Precision measurement of the W boson decay branching fractions in proton-proton collisions at root s=13 TeV - CMS Collaboration; Damarseçkin, Serdal (AMER PHYSICAL SOC, 2022)
The leptonic and inclusive hadronic decay branching fractions of the W boson are measured using proton-proton collision data collected at ffiffi s p ¼ 13 TeV by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of 35.9 fb−1. Events characterized by the production of one or two W bosons are selected and categorized based on the multiplicity and flavor of reconstructed leptons, the number of jets, and the number of jets identified as originating from the hadronization of b quarks. A binned maximum likelihood estimate of the W boson branching fractions is performed simultaneously in each event category. The measured branching fractions of the W boson decaying into electron, muon, and tau lepton final states are ð10.83 0.10Þ%, ð10.94 0.08Þ%, and ð10.77 0.21Þ%, respectively, consistent with lepton flavor universality for the weak interaction. The average leptonic and inclusive hadronic decay branching fractions are estimated to be ð10.89 0.08Þ% and ð67.32 0.23Þ%, respectively. Based on the hadronic branching fraction, three standard model quantities are subsequently derived: the sum of squared elements in the first two rows of the Cabibbo–Kobayashi–Maskawa (CKM) matrix P ij jVijj 2 ¼ 1.984 0.021, the CKM element jVcsj ¼ 0.967 0.011, and the strong coupling constant at the W boson mass scale, αSðm2 WÞ ¼ 0.095 0.033.
Keywords: P(P)OVER-BAR COLLISIONS